Five-year experience with donation after cardiac death kidney transplantation in a Canadian transplant program: Factors affecting outcomes - Moser, Michael; Sharpe, Michael; Weernink, Corinne; Brown, Harrison; McGregor, Thomas; House, Andrew; Luke, Patrick P. (Canadian Urological Association Journal, 2012)
Background: Donation after cardiac death (DCD) has led to an increase of up to 40% in the number of kidney transplants in some programs. Unfortunately, the increase in warm ischemic time results in higher rates of delayed graft function (DGF). The purpose of our study was to examine our initial 5-year experience with DCD kidney transplantation and to determine the factors involved in early postoperative function and function at 1 year. Methods: This retrospective study included a review of the recipient and donor charts of 63 DCD kidneys retrieved and transplanted by the London Multi-Organ Transplant Program between July 2006 and October 2011. Comparisons were carried out between our early (n=31, July 2006 to January 2009) and our recent experience (n=32, March 2009 to October 2011). DGF and creatinine clearance at 3, 7 and 365 days were examined with regression analyses. Results: DGF was seen in 65% of transplanted kidneys. Mean creatinine clearance (CrCl) at 1 year was 66.7 mL/min. Low pre-transplant recipient daily urine output was the most statistically significant predictor of DGF in multivariate analysis (p < 0.001). In comparisons between our early and more recent results, improvements were noted in time from asystole to flush (16.0 vs. 12.0 minutes, p = 0.003), while cold ischemic time increased (464 vs.725 minutes, p = 0.006). Experience contributed to a significant reduction in hospital length of stay (16 vs. 13 days, p = 0.035) and improved early renal function (CrCl at 3 days 7.8 vs. 11.9 mL/min, p = 0.027). The use of machine cold perfusion and higher recipient preoperative daily urine output predicted improved early renal function, while increasing donor age predicted poorer funcion at 1 year. Discussion: Despite early DGF, our results justify the continued transplantation of kidneys from DCD donors.